2016
DOI: 10.1039/c6ra23006g
|View full text |Cite
|
Sign up to set email alerts
|

4-Thiazolidinone derivatives: synthesis, antimicrobial, anticancer evaluation and QSAR studies

Abstract: A series of novel 4-thiazolidinone derivatives (1–18) was synthesized evaluated for its antimicrobial and anticancer potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…The formed precipitate was filtered off, dried and recrystallized from appropriate solvent to give target compounds. In case of no precipitate formed upon cooling, the solution was added to water and neutralized using Na 2 CO 3 solution, the formed precipitate was filtered, dried and recrystallized to obtain the expected thiazolidinone products (13)(14)(15)(16)(17)(18)(19)(20), respectively.…”
Section: General Procedures For the Synthesis Of 2-substituted-3-(quimentioning
confidence: 99%
See 1 more Smart Citation
“…The formed precipitate was filtered off, dried and recrystallized from appropriate solvent to give target compounds. In case of no precipitate formed upon cooling, the solution was added to water and neutralized using Na 2 CO 3 solution, the formed precipitate was filtered, dried and recrystallized to obtain the expected thiazolidinone products (13)(14)(15)(16)(17)(18)(19)(20), respectively.…”
Section: General Procedures For the Synthesis Of 2-substituted-3-(quimentioning
confidence: 99%
“…It has been reported that these derivatives possesses anti-tuberculosis [6,7], Antiplasmodial [4], Antibacterial [5], antihistamine [6], anticancer [11][12][13][14], anti-hypertensive [9], antifungal [10], antimalarial [11], anti-HIV [12] and antioxidant activities [13]. On the other hand, thiazole and thiazolidinone derivatives are known to exhibit diverse biological activities [14][15][16], they have anti-inflammatory [20,21], anticancer, antimicrobial [19], anti-tuberculosis [20] and antioxidant activity [21]. Inflammation is a fundamental physiological process that is ATEF M. AMER et al…”
Section: Introductionmentioning
confidence: 99%
“…[30] As various studies have revealed that some of the antimicrobial compounds having toxicity on bacteria display cytotoxic activity against cancer cells, [27][28][29] we evaluated the effect of the distance between the pyridinium nitrogen and the phenyl ring on the cytotoxic activity. [30] As various studies have revealed that some of the antimicrobial compounds having toxicity on bacteria display cytotoxic activity against cancer cells, [27][28][29] we evaluated the effect of the distance between the pyridinium nitrogen and the phenyl ring on the cytotoxic activity.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…[4] Autophagy is a physiological process that maintains cellular homeostasis by degrading and recycling organelles and proteins. [27][28][29] In our previous studies, oxime ether and hydrazone derivatives with quaternary pyridinium core were found to have remarkable antimicrobial and antileishmanial activities. On the contrary, autophagy may increase stress tolerance and survival in cancer cells under adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer screening results indicated that compound 24 (IC50 = 15.18 µM) was the most active anticancer agent and was more potent than the standard drug, carboplatin (IC50 > 100 µM). Antimicrobial activity results indicated that 25 was the most active antimicrobial agent (pMICec = 2.14 µM) and may serve as an important lead for the discovery of novel antimicrobial agents 20 . …”
mentioning
confidence: 99%